TEMPORAL COMPARISON OF WHEEZING PREVALENCE IN THE FIRST YEAR OF LIFE IN SÃO PAULO: INTERNATIONAL STUDY OF WHEEZING IN INFANTS - Aranda, Carolina Sanchez (Rev Paul Pediatr, 2018)
OBJECTIVE: To assess the prevalence and severity of wheezing in the first year of life of infants, using the standardized protocol of the Estudio Internacional de Sibilancias en Lactantes- phase 3, and compare the values obtained with those found in phase 1, conducted at the same center. METHODS: Between 2009 and 2010, parents and guardians of infants answered the written questionnaire of the Estudio Internacional de Sibilancias en Lactantes - phase 3, and its results were compared to those of phase 1, performed between 2005 and 2006. We divided the infants into wheezing and non-wheezing. The wheezing group was stratified according to the frequency of episodes: occasional wheezing - less than three -, and recurrent wheezing - three or more. RESULTS: Wheezing prevalence was similar in both phases (44.6 versus 46%). Regarding frequency, the prevalence of occasional wheezing increased (19.4 versus 23%; p=0.03) and recurrent wheezing decreased (26.7 versus 21.6%; p=0.005). Also, diagnosis of asthma (7.5 versus 21.8%), use of inhaled corticosteroids (11.7 versus35%), and hospitalization for wheezing (19.7 versus 32.6%) grew significantly in phase 3. This period coincides with the Influenza A (H1N1) pandemic, which could have contributed to this outcome. CONCLUSIONS: Wheezing prevalence in the first year of life remains high. Despite the temporal assessment showing a decrease in the prevalence of recurrent wheezing, a significant increase in its morbidity was identified due to the higher number of hospitalizations. In addition, there were signs of improvement in the wheezing management of infants, reflected by an increase in the diagnosis of asthma and a greater indication of preventive treatments.